An economic analysis of fertility and female labour force participation in New Zealand - Poot, Jacques; Siegers, Jacques (School of Management Working Papers, 1992)
This paper focusses on the regional variation in female labour force participation rates and fertility in New Zealand. The paper progresses beyond earlier work by pooling regional cross-sections of three censuses, by addressing causality in the linkage between fertility and labour force participation explicitly and by testing for structural change in the behavioural equations. The empirical results provide suppon for the neoclassical demand system approach to fertility and labour force participation, in which both are influenced, but in opposite ways, by income and prices (primarily the real wage) and a range of socio-economic controls, which account for regional composition and demand-side effects. It is also found that female labour force participation and fertility became less elastic with respect to male income and the female hourly wage over the 1976-86 decade. This phenomenon is attributed to sharply rising female labour force participation, a decline in the 1FR, a greater time input of males in non-market work and changes in the home production technology.